Trajectories : prosopographic approach of French explorers of Africa and Asia (1870-1914) - (:unkn) unknown (My University, 2016)
This thesis presents the interest of studying in a comprehensive and general way, rather than in a fragmented one, the mid of French explorers in the late nineteenth century, to discover more deeply their personalities, motivations, curricula that led them to exploration, the missions they have accomplished, the results they have achieved, etc. This thesis is also the means of establishing a true historical sociology of explorers addressing this environment in its totality and complexity, obviously taking account of the most famous ones but also by focusing on those whose names have been forgotten, ignored or little discussed. This work put into perspective and issues comparisons between explorers who have evolved in various geographic areas and at different periods. Moreover, these explorers would not have existed without support, without network, without support of intellectual, economic and financial, political, scientific connections... This thesis also is the opportunity to uncover the existence of these networks of influence and of colonial enterprise, to discover the means of action and to highlight the means of their business. In this sense, this study makes us understand from the inside both field missions and their sponsors more or less interested in exploration. Overall, this thesis not only helps to better understand what is called the phenomenon of colonization, through a better understanding of the main players, but highlights a completely original fraction and little known of the French society.
Keywords: African Research